Range of protein induced by vitamin K absence or antagonist-II levels in neonates at birth - Sameshima, Tomohiro; Ashina, Mariko; Fukuda, Takuya; Kido, Takumi; Abe, Shinya; Watanabe, Yuko; Sato, Itsuko; Yano, Yoshihiko; Tanimura, Kenji; Nagase, Hiroaki; Nozu, Kandai; Fujioka, Kazumichi (Scientific reports, 2024)
Protein induced by vitamin K absence or antagonist-II (PIVKA-II) is avitamin K (VK) deficiency indicator in neonates. However, PIVKA-II detection frequency in neonatal blood at birth and the correlation between PIVKA-II and gestational age are unclear. We retrospectively analyzed infants admitted to our institution between June 1, 2018, and March 31, 2022, whose clinical and PIVKA-II data were available, and classified them into preterm and term infant groups. Overall incidence of PIVKA-II-positive cases (≥ 50 mAU/mL) was 42.8%, including 0.6% apparent VK deficiency (≥ 5000 mAU/mL), 3.1% experimental VK deficiency (1000–4999 mAU/mL), and 10.7% latent VK deficiency (200–999 mAU/mL) cases. Incidence of PIVKA-II-positive cases was significantly higher in the term group than in the preterm group (49.4% vs. 29.7%, p < 0.001). Gestational age correlated with PIVKA-II levels (r 2 = 0.117, p < 0.0001). Median serum PIVKA-II levels and incidence of PIVKA-II-positive cases (≥ 50 mAU/mL, 16.4%) were lower at 5 days after birth than at birth, possibly reflecting the postnatal VK prophylaxis impact. Only one infant was diagnosed with VK deficiency bleeding (PIVKA-II levels, at birth: 10,567 mAU/mL; at day 5: 2418 mAU/mL). Thus, serum PIVKA-II levels after birth weakly correlated with gestational age. VK deficiency was more common in term infants than in preterm infants.